A Modified Model for Kinetic Analysis of Petroleum Coke - Iman Eslami Afrooz; Dennis Ling Chuan Ching (International Journal of Chemical Engineering)
In this study, a nonisothermal kinetics analysis of petcoke was performed at heating rates of 10, 15, and 20°C/min using thermal gravimetric analysis (TGA). The behaviour of petcoke at different gasification stages (dewatering, volatilization, char burning, and burnout) was studied. The effect of heating rate on the activation energy of petcoke gasification was also investigated. The activation energy of petcoke was estimated using different kinetic models that include volume reaction model (VRM), shrinking core model (SCM), random pore model (RPM), Coats and Redfern model (CRM), and normal distribution function (NDF). The NDF model was modified in this study. It was found that the experimental data were best fitted with the modified normal distribution function (MNDF) and SCM. The results also showed that activation energy decreases as heating rate increases, leading to reduction in gasification completion time.